Molecular Changes in the Nasal Cavity after N,N-Dimethyl-p-toluidine Exposure - Dunnick, June K. (Toxicol Pathol, 2016)
N,N-Dimethyl-p-toluidine (DMPT) (Cas No. 99-97-8), an accelerant for methyl methacrylate monomers in medical devices, is a nasal cavity carcinogen in a 2-year cancer study in male and female F344/N rats, with the nasal tumors arising from the transitional cell epithelium. In this study we exposed male F344/N rats for five days to DMPT (0, 1, 6, 20, 60 or 120 mg/kg (oral gavage)) to explore early changes in the nasal cavity after short-term exposure. Lesions occurred in the nasal cavity including hyperplasia of transitional cell epithelium (60 and 120 mg/kg). Nasal tissue was rapidly removed and preserved for subsequent laser capture microdissection and isolation of the transitional cell epithelium (0 and 120 mg/kg) for transcriptomic studies. DMPT transitional cell epithelium gene transcript patterns were characteristic of an anti-oxidative damage response (e.g. Akr7a3, Maff, Mgst3), cell proliferation, and decrease in signals for apoptosis. Amino acid transporters transcripts were upregulated (e. g, Slc7a11). The DMPT nasal transcript expression pattern was similar to that found in the rat nasal cavity after formaldehyde exposure with over 1000 transcripts in common. Molecular changes in the nasal cavity after DMPT exposure suggest that oxidative damage is a mechanism for the DMPT toxic and/or carcinogenic effects.